Impact of school eye care intervention on the academic performance of school children in Katsina State, Nigeria - Yusuf, Muhammad; Rabiu, Mansur Muhammad; Taryam, Manal Omran; Azu, Nnanna Philemon (Journal of Asian Scientific Research, 2024)
This study aims to examine the impact of the Noor Dubai Foundation (NDF) School Eye Intervention on the academic performance of schoolchildren in Katsina State. The survey research design was utilised, and primary data was collected using a five-point Likert questionnaire on the beneficiaries. Both tables, graphs, and regression were used to analyse the data. The results reveal that 65.13% of the respondents indicated their vision had improved, 61.11% revealed their reading skills had improved, 64.32% revealed their communication skills had improved, and 64.71% showed their comprehension ability had improved after the eye intervention program. More so, 58.54% revealed their exam score performance had improved, and 59.29% indicated that their positions in the class had improved after receiving the NDF eye care intervention in the state. The analysis of the impact of the NDF programme reveals that eye treatment rather than eye screening improves pupils' performance. This implies that NDF school eye intervention has significantly improved students' academic performance after receiving eye treatment and eyeglasses. The policy implication is that poor eye health affects the realisation of schoolchildren's right to education. The government should emphasise partnering and collaborating with the NDF on eye care interventions for sustainable vision and quality education.